2019
DOI: 10.1177/1938965519892907
|View full text |Cite
|
Sign up to set email alerts
|

A Micro-Level View of CSR: A Hospitality Management Systematic Literature Review

Abstract: This study provides a systematic review of corporate social responsibility (CSR) in the hospitality management literature over the last decade. In contrast to prior reviews, this article starts from a broader analysis, followed by a narrower, micro-level examination of the hospitality management literature that links CSR to customers’ and employees’ attitudes and behaviors. The findings of this review show that researchers study CSR primarily from a meso-level perspective of how CSR is developed and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 181 publications
2
67
0
Order By: Relevance
“…Hence, the present study establishes that MCSR has a positive relationship with employees’ pro-environmental behavior. This finding is also supported by contemporary CSR researchers [ 25 , 51 , 52 ]. The study further confirmed that the role of females is very important to achieve sustainability objectives because females are found to be more inclined towards environment management.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Hence, the present study establishes that MCSR has a positive relationship with employees’ pro-environmental behavior. This finding is also supported by contemporary CSR researchers [ 25 , 51 , 52 ]. The study further confirmed that the role of females is very important to achieve sustainability objectives because females are found to be more inclined towards environment management.…”
Section: Discussionsupporting
confidence: 84%
“…It is believed that CSR at a narrower or micro-level can be effective in dealing with environmental issues [ 51 ]. The healthcare sector being labor-intensive can make their employees behave in ways that cast a considerable impact on overall environmental improvement.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Different researchers acknowledge the importance of employees to successfully implement various CSR-related programs [ 15 , 16 , 17 ]. Hence, employee engagement in CSR activities assures that such actions become part of corporate culture and DNA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, research in the hospitality literature shows that CSR activities have a positive influence on attracting and retaining employees (Guzzo et al, 2019). Future research in this area can manipulate company involvement in CSR activities using fictitious websites to influence perceived fit and organizational attraction among prospective applicants with varying attitudes of CSR.…”
Section: Discussionmentioning
confidence: 99%